Rhetoric and realities of regional integration: Botswana SME perspectives on Southern African trade - A. O. Thomas; E. Marandu (South African Journal of Business Management, 2017)
Despite political pronouncements about facilitating development through economic integration of geographic regions in Africa, intra-regional trade remains limited and unbalanced. While tariff barriers have declined within Southern Africa, non-tariff trade barriers to export-import growth persist, impacting on the smaller economies. Utilising interviews with small-to-medium enterprises in land-locked Botswana, this study generated in-depth qualitative data on their experience of barriers to trading regionally. The research found that administrative procedures at the national level, ambiguity of implementation at borders and constraints on logistics constitute their most daunting impediments. Among the key imperatives then for effective regional integration and economic growth among developing countries in Africa and elsewhere are standards harmonization, regulatory streamlining, process transparency and improvement of infrastructure.
Keywords: 650